Optimising organ perfusion in the high-risk surgical and critical care patient: a narrative review. (August 2019) - Parker, Thomas; Brealey, David; Dyson, Alex; Singer, Mervyn
Summary: Maintenance or prompt restoration of an oxygen supply sufficient to facilitate adequate cellular metabolism is fundamental in maintaining organ function. This is particularly relevant when metabolic needs change markedly, for example in response to major surgery or critical illness. The consequences of inadequate tissue oxygenation include wound and anastomotic breakdown, organ dysfunction, and death. However, our ability to identify those at risk and to promptly recognise and correct tissue hypoperfusion is limited. Reliance is placed upon surrogate markers of tissue oxygenation such as arterial blood pressure and serum lactate that are insensitive to early organ compromise. Advances in oxygen sensing technology will facilitate monitoring in various organ beds and allow more precise titration of therapies to physiologically relevant endpoints. Clinical trials will be needed to evaluate any impact on outcomes, however accurate on-line monitoring of the adequacy of tissue oxygenation offers the promise of a paradigm shift in resuscitation and perioperative practice. This narrative review examines current evidence for goal-directed therapy in the optimisation of organ perfusion in high-risk surgical and critically ill patients, and offers arguments to support the potential utility of tissue oxygen monitoring.